Preparation of Ultrahigh Potential Gradient of ZnO Varistors by Rare-Earth Doping and Low-Temperature Sintering. (3rd February 2013) - Ke, Lei; Hu, Ming; Ma, Xueming
Abstract : The effects of rare-earth doping and low-temperature sintering on electrical properties of ZnO varistors were investigated. The potential gradient ( E 1 m A ) of the ZnO varistors increased significantly to 2247.2 V/mm after doping 0.08 mol% of Y2 O3 and sintering at 800°C for 2 h. The notable decrease of the grain size with the given experimental conditions was the origin for the increase in E 1 m A . During the process of high-temperature sintering, both the oxygen at the grain boundary interface and the neutralisation of the ions on the depletion layer were directly reduced, which caused the weight loss and the internal derangement of double Schottky barriers.